Theoretical prerequisites for the formation of the social responsible development - Bielienkova О. (Ways to Improve Construction Efficiency, 2018)
The origin and interrelation of the concepts of "development", "socially responsible development" and the differences between the terms "developer", "customer", "builder", "investor" are analyzed. In the domestic legislative framework the concept of "development" is currently absent. The current legislation operates with the terms "customer", sometimes "developer", "investor", "general contractor", "subcontractor" and other participants in construction.It is proposed as the main idea of the development to use the concept of sustainable development – to meet the needs of the present generation, which does not undermine the ability to meet the needs of future generations.New concepts of "socially responsible real estate development" are proposed – development of construction on the basis of awareness of modern and future economic, social and environmental consequences for investors of real estate, other stakeholders, the population, the whole society and the environment, "environmentally oriented real estate" aimed at reducing environmental impact (green building, zero energy homes, use of eco-friendly materials, etc.) and "socially oriented development" – real estate development is aimed at developing the social component (development of accessibility of housing, infrastructure, accessibility for small mobile population groups), etc.